UPAYA PIHAK SEKOLAH DALAM MENGATASI KESULITAN MEMBACA SISWA DI SMP N 6 PASAMAN - Wahyu Nengsih; Harisnawati Harisnawati; Sri Rahayu (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Reading ability is a basic competency that is very important for every student to have because it plays a foundation in understanding learning materials in various subjects. However, in reality, there are still students at the Junior High School (SMP) level who experience reading difficulties which affect their learning process and outcomes. This study aims to describe various efforts made by the school to overcome students' reading difficulties at SMP Negeri 6 Pasaman. The study used a qualitative approach with a descriptive research type. Research informants consisted of the principal, vice principal for student affairs, vice principal for curriculum, homeroom teachers, subject teachers, and students who experienced reading difficulties. Data collection was carried out through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the reading difficulties experienced by students include low ability to understand the content of reading, lack of reading fluency, difficulty reading new vocabulary, pronunciation errors, a tendency to repeat words when reading, difficulty reading texts with close letter spacing, and not being able to write sentences from dictation. To address these issues, the school implemented various strategies, including strengthening coordination and collaboration between school stakeholders, implementing learning strategies and models tailored to student needs, organizing scheduled reading tutoring programs, and developing a culture of literacy through the provision of supporting facilities. These efforts have positively contributed to improving reading skills and fostering students' confidence in participating in learning activities. Keywords: reading difficulties, school, literacy.   Abstrak: Kemampuan membaca merupakan kompetensi dasar yang sangat penting dimiliki oleh setiap peserta didik karena berperan sebagai fondasi dalam memahami materi pembelajaran pada berbagai mata pelajaran. Namun, kenyataannya masih terdapat siswa di tingkat Sekolah Menengah Pertama (SMP) yang mengalami kesulitan membaca sehingga memengaruhi proses dan hasil belajar mereka. Penelitian ini bertujuan untuk mendeskripsikan berbagai upaya yang dilakukan pihak sekolah dalam mengatasi kesulitan membaca siswa di SMP Negeri 6 Pasaman. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Informan penelitian terdiri atas kepala sekolah, wakil kepala sekolah bidang kesiswaan, wakil kepala sekolah bidang kurikulum, wali kelas, guru mata pelajaran, serta siswa yang mengalami kesulitan membaca. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan tahapan reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kesulitan membaca yang dialami siswa meliputi rendahnya kemampuan memahami isi bacaan, kurangnya kelancaran membaca, kesulitan membaca kosakata baru, kesalahan dalam pelafalan, kecenderungan mengulang kata saat membaca, kesulitan membaca teks dengan jarak huruf yang rapat, serta belum mampu menuliskan kalimat hasil dikte. Untuk mengatasi permasalahan tersebut, pihak sekolah menerapkan berbagai strategi, antara lain memperkuat koordinasi dan kolaborasi antarpihak sekolah, menerapkan strategi serta model pembelajaran yang disesuaikan dengan kebutuhan siswa, menyelenggarakan program les baca secara terjadwal, dan mengembangkan budaya literasi melalui penyediaan fasilitas pendukung. Berbagai upaya tersebut memberikan kontribusi positif terhadap peningkatan kemampuan membaca sekaligus menumbuhkan rasa percaya diri siswa dalam mengikuti kegiatan pembelajaran. Kata kunci: kesulitan membaca, pihak sekolah, literasi